Risk, reliability and sustainable remediation in the field of civil and environmental engineering - Roshni, Thendiyath; Samui, Pijush, 1978-; Tien Bui, Dieu; Kim, Dookie, 1969-; Khatibi, Rahman (Elsevier, 2022)
Risk, Reliability and Sustainable Remediation in the Field of Civil and Environmental Engineering illustrates the concepts of risk, reliability analysis, its estimation, and the decisions leading to sustainable development in the field of civil and environmental engineering. The book provides key ideas on risks in performance failure and structural failures of all processes involved in civil and environmental systems, evaluates reliability, and discusses the implications of measurable indicators of sustainability in important aspects of multitude of civil engineering projects. It will help practitioners become familiar with tolerances in design parameters, uncertainties in the environment, and applications in civil and environmental systems. Furthermore, the book emphasizes the importance of risks involved in design and planning stages and covers reliability techniques to discover and remove the potential failures to achieve a sustainable development.
Keywords: Civil engineering.; Environmental engineering.; Sustainable development.; Risk management.; elektronické knihy; electronic books